Peningkatan Hasil Belajar Sikap Lilin Melalui Metode Latihan Senam Lantai Siswa Kelas V SD Naskat Masnana Bursel - Lilipaly, Dortje; Unmehopa, Wilhelmina (MANGGUREBE: Journal Physical Education, Health and Recreation, 2022)
The Classroom Action Research on fourth grade students at Naskat Masnana Elementary School, South Buru Regency with a background of preliminary observations shows that students' ability to practice the candle attitude is still low. So that some students are still not able to do waxing properly because they make mistakes, while the mistakes that occur are: Many fingers do not support the waist, what often happens is the waist is supported by the thumb. not strong enough to support the waist. When lifting the legs, both legs that are straight up are leaned back, so it is heavy to support and cannot last long. This research was conducted with the aim of improving the learning outcomes of the candle stance in floor exercise through training methods. The research method used is Classroom Action Research (CAR). The research was carried out in two cycles, the first cycle consisting of action planning, action implementation, action observation, reflection, and the second cycle which was associated with the results achieved in the first cycle. The subjects in this study were fourth grade students at SD Naskat Masnana, South Buru Regency, totaling 24 male students, 14 female students. The data collection carried out in this study was observation, interviews, documentation. Based on the analysis of learning activities above, the total learning value in cycle I was 70.32% and the total learning value in cycle II was 79.08%. From the results of the calculations above, there was an increase in learning in cycle II of 8.76%. Based on the results of observations during the learning process in class, it turns out that the training method is effective in improving learning outcomes for wax attitudes. the hypothesis in this classroom action research is acceptable, meaning that the learning outcomes of floor gymnastics can be improved through the exercise method in fourth grade students at SD Naskat Masnana Bursel.